2020
DOI: 10.3389/fpls.2020.619589
|View full text |Cite
|
Sign up to set email alerts
|

Priming by Timing: Arabidopsis thaliana Adjusts Its Priming Response to Lepidoptera Eggs to the Time of Larval Hatching

Abstract: Plants can respond to eggs laid by herbivorous insects on their leaves by preparing (priming) their defense against the hatching larvae. Egg-mediated priming of defense is known for several plant species, including Brassicaceae. However, it is unknown yet for how long the eggs need to remain on a plant until a primed defense state is reached, which is ecologically manifested by reduced performance of the hatching larvae. To address this question, we used Arabidopsis thaliana, which carried eggs of the butterfl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 105 publications
(117 reference statements)
4
44
0
Order By: Relevance
“…In this study, ROS accumulation and cell death were induced in all plant species tested, whereas the strong HR-like necrosis and high PR1 expression was specific to B. nigra and to Pierinae insect species. It is possible that also in other species and accessions in the Brassicaceae that we have not investigated closely, a general immune response lacking a strong cell death is activated by Pieris eggs, as was shown for A. thaliana (Col-0) (Gouhier-Darimont et al, 2013, 2019Stahl et al, 2020;Valsamakis et al 2020). Our data suggest that the strong HR-like necrosis is always accompanied by ROS and high PR1 expression.…”
Section: Molecular and Cellular Responses To Insect Eggsmentioning
confidence: 50%
“…In this study, ROS accumulation and cell death were induced in all plant species tested, whereas the strong HR-like necrosis and high PR1 expression was specific to B. nigra and to Pierinae insect species. It is possible that also in other species and accessions in the Brassicaceae that we have not investigated closely, a general immune response lacking a strong cell death is activated by Pieris eggs, as was shown for A. thaliana (Col-0) (Gouhier-Darimont et al, 2013, 2019Stahl et al, 2020;Valsamakis et al 2020). Our data suggest that the strong HR-like necrosis is always accompanied by ROS and high PR1 expression.…”
Section: Molecular and Cellular Responses To Insect Eggsmentioning
confidence: 50%
“…Levels of SA were significantly enhanced in previously egg-treated elm leaves after a larval feeding period of 24 h. Similarly, significantly enhanced SA levels were detected in A. thaliana when laden with eggs by the butterfly Pieris brassicae and subsequently damaged by its hatching larvae for 24 h (Lortzing et al 2019 ; Valsamakis et al 2020 ). In contrast, moth egg depositions upon the annual species Nicotiana attenuata and the perennial S. dulcamara did not affect SA levels in subsequently larval feeding-damaged leaves (Drok et al 2018 ).…”
Section: Discussionmentioning
confidence: 94%
“…For instance, higher JA levels were detected in egg-treated tomato plants 30 min and 60 min after wounding (Kim et al 2012 ). In Arabodpsis thaliana , Valsamakis et al ( 2020 ) found enhanced JA-Ile levels in egg-treated leaves after a 3 h larval feeding period when compared to egg-free, feeding-damaged leaves, but not after a 12 h feeding period. Future studies will need to investigate whether previously egg-laden elm leaves show enhanced JA levels very early on after the onset of larval feeding.…”
Section: Discussionmentioning
confidence: 99%
“…These responses were shown to be dependent on EDS1, ISOCHORISMATE SYNTHASE 1/SALICYLIC ACID INDUCTION DEFICIENT 2 (ICS1/SID2) and, partially, (NONEXPRESSER OF PR GENES 1) (NPR1), which are known signaling components of plant defense responses against biotrophic pathogens [26]. Transcriptomics studies in different plants species have con rmed that insect oviposition induces genes associated with SA-and ROS-mediated immune responses and PR1 gene expression [15,24,[27][28][29][30][31][32][33], including in B. nigra and B. rapa [21,34,35]. It is suggested that there is a conserved transcriptional response amongst different plant-insect eggs interactions [36].…”
Section: Introductionmentioning
confidence: 99%